(untitled) (The Pakistan Development Review, 1995)
Although still ‘invisible’ to policy-makers, women’s involvement in agricultural and livestock production is empirically established through national surveys and intensive studies. The labour force participation rates for rural women in 1990-91 varied ranged between 57 percent (Agricultural Census) and 43 percent (Pakistan Integrated Household Survey). Evidence from micro studies also shows that women are active participants in the farm and livestock sectors [Freedman and Wai (1988); Masood (1988); Ali et al. (1976); Haque (1986); Khan and Bilquees (1976)]. While rural women’s contribution to agricultural and livestock production is well-documented, they have little or no access to productive inputs to enhance their economic participation in these sectors. Evidence based on national level data indicates that women’s participation in agricultural activities is constrained by the lack of land and other assets [Sathar and Desai (1994)]. Contrary to the general view, women belonging to households that own land or other assets have a higher labour force participation rate than landless women. While landless women are more likely to work as agricultural labourers, however, the demand for wage employment is seasonal, limited to a few activities and certain regions, and their lack of assets to work with excludes any possibility of self-employment. Findings of village level research indicate a wide gap between the technology used by rural women and the more efficient practices in livestock production, which is attributed to their lack of contact with extension services and to their lack of resources to adopt more efficient methods of livestock care [Haque (1986)].